(untitled) (Bangladesh Journal of Pharmacology, 2024)
The study was designed to evaluate the antiproliferative effects of Nigella sativa plant ethanol extract against MDA-MB-231 triple-negative breast cancer cells. DAPI and annexin V/propidium iodide staining assays were used to examine apoptosis. Results showed that N. sativa extract significantly (p<0.05) impeded the growth of MDA-MB-231 cells, with IC50 of 12.5 μg/mL. The colony-forming potential of MDA-MB-231 was significantly (p<0.05) decreased by the N. sativa extract-induced apoptosis. Increased expression of Bax, caspase-3, cleaved caspase-3, and cleaved PARP was also observed in the extract-treated MDA-MB-231 cells. Moreover, flow cytometric analysis showed that N. sativa extract triggered G0/G1 phase arrest in MDA-MB-231 cells. Collectively, N. sativa extract exhibits potent antiproliferative activity against triple-negative breast cancer cells and may be used as a source of anti-cancer agents.